A comprehensive review of the multifaceted role of the microbiota in human pancreatic carcinoma. (November 2022) - Pandya, Gouri; Kirtonia, Anuradha; Singh, Aishwarya; Goel, Arul; Mohan, Chakrabhavi Dhananjaya; Rangappa, Kanchugarakoppal S; Pandey, Amit Kumar; Kapoor, Sonia; Tandon, Simran; Sethi, Gautam; Garg, Manoj
Abstract: Pancreatic carcinoma is associated with one of the worst clinical outcomes throughout the globe because of its aggressive, metastatic, and drug-resistant nature. During the past decade, several studies have shown that oral, gut, and tumor microbiota play a critical role in the modulation of metabolism and immune responses. Growing pieces of evidence have proved beyond a doubt that the microbiota has a unique ability to influence the tumor microenvironment as well as the metabolism of chemotherapeutic agents or drugs. Given this, microbiota, known as the ecological community of microorganisms, stands to be an avenue of quality research. In this review, we provide detailed and critical information on the role of oral, gut, and pancreatic microbiota disruptions in the development of pancreatic carcinoma. Moreover, we comprehensively discuss the different types of microbiota, their potential role, and mechanism associated with pancreatic carcinoma. The microbiome provides the unique opportunity to enhance the effectiveness of chemotherapeutic agents and immunotherapies for pancreatic cancer by maintaining the right type of microbiota and holds a promising future to enhance the clinical outcomes of patients with pancreatic carcinoma.